2015
DOI: 10.1515/jppr-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterization of the causal agent of chafer beetle mortality in the wheat fields of the Kurdistan province, Iran

Abstract: We report the first case of chafer beetle [Anisoplia austriaca(Herbst 1783)] mortality caused byActinomucor elegansvar.elegansin wheat fields of the Kurdistan province, Iran. For three years, dead larvae ofAnisoplia austriacawere collected from wheat fields of the Kurdistan province. Similar isolates of a fast-growing fungus were recovered from all samples. The fungal isolates were identified asA. elegansvar.elegansbased on morphological and cultural characteristics. The identity of the species was further con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, for most species, the data are not sufficient to accurately assess their ecological niche or geographic distribution. For example, Actinomucor elegans was thought to be a saprotrophic soil fungus [131] until it was shown that it efficiently infects chafer beetle [132]. Even from the existing data, it can be safely concluded that the Mucorales are ecologically highly diverse.…”
Section: Ecology and Geographic Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for most species, the data are not sufficient to accurately assess their ecological niche or geographic distribution. For example, Actinomucor elegans was thought to be a saprotrophic soil fungus [131] until it was shown that it efficiently infects chafer beetle [132]. Even from the existing data, it can be safely concluded that the Mucorales are ecologically highly diverse.…”
Section: Ecology and Geographic Distributionmentioning
confidence: 99%
“…Most of our information on the ecology and distribution of species is based on the source provided by culture collections and clinical studies. The number of studies directly addressing the natural habitats of Mucorales [132,[136][137][138][139][140] is very limited. Taxa such as Apophysomyces, Saksenaea, and Mucor circinatus (misapplied: Circinella simplex) seem to show a distribution in tropical and subtropical regions.…”
Section: Ecology and Geographic Distributionmentioning
confidence: 99%
“…A. elegans var. elegans has been reported as a potential biocontrol agent against the chafer beetle [ 11 ].…”
mentioning
confidence: 99%
“…Thus, the information regarding the taxonomy and ecology of Mucoromycota could advance considerably if there were more taxonomists willing to do inventories of these fungal species, specifically in poorly or unexplored habitats/hosts (Hawksworth and Rossman 1997 ; Hawksworth 2001a , b ; Aime and Brearley 2012 ), thereby revealing unforeseen ecological interactions. For example, the well-known saprotrophic fruit parasite, Gilbertella persicaria (Mehrotra 1963a , 1963b ; Guo et al 2012 ; Pinho et al 2014 ), was found infecting the black tiger shrimp ( Penaeus monodon ) (Karthikeyan and Gopalakrishnan 2014 ), while Actinomucor elegans , a saprotrophic soil fungus, which is occasionally involved in causing mucormycosis, has been reported to infect chafer beetle (Karimi et al 2015 ). This fungus has also been found in a mutualistic association with Abutilon theophrasti roots (Kia et al 2014 ).…”
Section: Species Conceptsmentioning
confidence: 99%